(untitled) (Fiep Bulletin - online, 2014)
Introduction : The history and practice of massage are cited in many literatures specific empirically . Without the foundation of their origin , that is lost in time . The knowledge was passed through images made ??by oriental rugs on looms , Greek vases , cave paintings , drawings on parchment , situations such as bruising a body part , have a habit of rubbing the area with your hands , a practice that is a natural methods of healing humanity’s oldest and is present in the areas of medicine , sport and aesthetics ( NESSI. 2003) . Objective: To investigate the effects and physiological benefits of massage through the theory and practice for the welfare decrease stress . Methodology : With the lifting of more than 300 publications in Portuguese and other languages ??on massage are known physiological effects on the human body and mind , reducing the harmful effects of stress are present in all of them , the main quotes ( IBÁÑEZ , 1993; NeSSI , 2003; Gallego , 1996; Bentley, 2006; BOIGEY , 1986; Atkinson , 2000) here reported : muscle relaxation , removal of catabolic ; decreased muscle fatigue improvement in viscosity between the fascia ; stimulation of elastin and collagen , improves arterial and venous circulation , increased sensitivity fine , reduction of cutaneous adhesions ; sedative and analgesic effects , stimulation of gastrointestinal transit ; aid in metabolic exchanges and energy ; action on bronchial obstruction , increased motion; increased body awareness , aid in recovery post workout ; decrease in thickness of tissue ; balance between sympathetic and parasympathetic ; produce emotional benefits and stress reduction . Conclusion : We conclude that massage performed correctly following the principles of Hippocrates and Herodotus (Wood , 1984; CASSAR , 2001) , such as soft start , deepen and smooth finish , with movements such as landslides , friction , kneading and percussion . May decrease the actions of stress , improving quality of life , promoting the welfare . Result of the research was the publication of the Book relieving Massage - Theory and Practice for the welfare . 1st edition in 2003 and 5th in 2010 , having a direct reach of 10.000 voters